Case Report: Optimizing Pre- and Intraoperative Planning With Hyperaccuracy Three-Dimensional Virtual Models for a Challenging Case of Robotic Partial Nephrectomy for Two Complex Renal Masses in a Horseshoe Kidney - Campi, Riccardo; Sessa, Francesco; Rivetti, Anna; Pecoraro, Alessio; Barzaghi, Paolo; Morselli, Simone; Polverino, Paolo; Nicoletti, Rossella; Li Marzi, Vincenzo; Spatafora, Pietro; Sebastianelli, Arcangelo; Gacci, Mauro; et al. (Frontiers in Surgery, 2021)
Objective: To report a case of robot-assisted partial nephrectomy (RAPN) for two highly complex renal tumors in a patient with a Horseshoe kidney (HSK), focusing on the utility of hyperaccuracy three-dimensional (HA3D) virtual models for accurate preoperative and intraoperative planning of the procedure. Methods: A 74-year-old Caucasian male patient was referred to our Unit for incidental detection of two complex renal masses in the left portion of a HSK. The 50 × 55 mm, larger, predominantly exophytic renal mass was located at the middle-lower pole of the left-sided kidney (PADUA score 9). The 16 × 17 mm, smaller, hilar renal mass was located at the middle-higher pole of the left-sided kidney (PADUA score 9). Contrast-enhanced CT scan images in DICOM format were processed using a dedicated software to achieve a HA3D virtual reconstructions. RAPN was performed by a highly experienced surgeon using the da Vinci Si robotic platform with a three-arm configuration. A selective delayed clamping strategy was adopted for resection of the larger renal mass while a clampless strategy was adopted for the smaller renal mass. An enucleative resection strategy was pursued for both tumors. Results: The overall operative time was 150 min, with a warm ischemia time of 21 min. No intraoperative or postoperative complications were recorded. Final resection technique according to the SIB score was pure enucleation for both masses. At histopathological analysis, both renal masses were clear cell renal cell carcinoma (ccRCC) (stage pT1bNxMx and pT3aNxMx for the larger and smaller mass, respectively). At a follow-up of 7 months, there was no evidence of local or systemic recurrence. Conclusions: Surgical management of complex renal masses in patients with HSKs is challenging and decision-making is highly nuanced. To optimize postoperative outcomes, proper surgical experience and careful preoperative planning are key. In this regard, 3D models can play a crucial role to refine patient counseling, surgical decision-making, and pre- and intraoperative planning during RAPN, tailoring surgical strategies and techniques according to the single patient's anatomy.